1977
DOI: 10.1210/jcem-45-4-818
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Antidiuretic Hormone and Other Hormones Through the Dialysis Membrane in Patients Undergoing Chronic Hemodialysis

Abstract: In eight patients undergoing chronic hemodialysis, ultrafiltration was performed for 1 h in each patient. The concentration of urea nitrogen, creatinine, ADH, cortisol, GH, prolactin and TSH was measured in plasma and the filtering solution, and the permeability of each substance was determined. The plasma concentration of ADH coincided with that of the filtering solution, and no significant difference was noted between the permeability of creating and ADH. In contrast, cortisol, GH, prolactin and TSH were not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
12
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 10 publications
2
12
0
Order By: Relevance
“…This study confirms that plasma AVP is totally filtered through hemofiltration membranes, as previously reported for hemodialysis membranes by Shimamoto et al (3). The mean basal plasma AVP level was 7.2 ± 0.6 pg/ ml in their patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This study confirms that plasma AVP is totally filtered through hemofiltration membranes, as previously reported for hemodialysis membranes by Shimamoto et al (3). The mean basal plasma AVP level was 7.2 ± 0.6 pg/ ml in their patients.…”
Section: Discussionsupporting
confidence: 91%
“…The permeability of arginine vasopressin (AVP) through such a membrane was found to be similar to that of urea and creatinine (3). We, therefore, thought it of interest to study the response of plasma AVP to a forced increase in its MCR under controlled conditions in the absence of the usual stimuli of AVP secretion.…”
mentioning
confidence: 99%
“…At present, however, no clear conclusion can be drawn on whether AVP is removed in substantial amounts by HD. One study has reported similar plasma AVP concentrations in the in- and outgoing blood before and after the dialyzer during HD [69], suggesting that there is no significant clearance of AVP, whereas two other studies detected AVP in the ultrafiltrate [37,70], suggesting that there is at least some removal of AVP by HD. Systematic data on AVP clearance by dialyzers are lacking.…”
Section: Potential Mechanism Of the Relative Avp Deficiency During Hdmentioning
confidence: 99%
“…Results of protocols (b) and (c) elucidated the possible reasons for [ 15] noted variable levels of PAVP after UF, but as a group, the mean levels were not different before and after UF. Vaziri et al [13] showed actual lower PAVP in patients with CRF at the end of 1 h of hemofiltration.…”
Section: Discussionmentioning
confidence: 87%
“…The hormone is metabolized mainly in the liver [4] and kidneys [5], with less than 10% of the intact hormone excreted in the urine [6], As with other hormones [7], plasma vasopressin level and its metabolism appears to be altered in subjects with chronic renal failure (CRFj-Scanty literature is available on the role, fate, and regulation of vasopressin in patients with CRF [8][9][10][11][12][13][14], Uniformly, these reports suggested that the plasma AVP (PAVP) was elevated in the majority of subjects with CRF before onset of the hemodialysis and lower at the end of procedure. A few authors suggested that the elevated levels were due to lack of functioning kidneys [8][9], lack of ability of artificial kidneys to filter PAVP [14] and/or abnormal regulation of vasopressin to volume and osmotic stimuli in CRF [10], One report suggested that the artificial kidneys were quite capa ble of filtering the AVP [15], To clarify the situation, 1 A preliminary report of these studies was published as an abstract in the Programme of the 65th Annual Meeting of the Endocrine Society, 1983. This work was supported by the Merit Review grant of the Veterans' Administration to M. Ilusain Jawadi, MD.…”
mentioning
confidence: 99%